2014
DOI: 10.1016/j.nbd.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of allosteric modulators of GPCRs for treatment of CNS disorders

Abstract: The discovery of allosteric modulators of G protein-coupled receptors (GPCRs) provides a promising new strategy with potential for developing novel treatments for a variety of central nervous system (CNS) disorders. Traditional drug discovery efforts targeting GPCRs have focused on developing ligands for orthosteric sites which bind endogenous ligands. Allosteric modulators target a site separate from the orthosteric site to modulate receptor function. These allosteric agents can either potentiate (positive al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
163
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(167 citation statements)
references
References 312 publications
(380 reference statements)
4
163
0
Order By: Relevance
“…These selective mGlu 5 NAMs have shown exciting efficacy across preclinical models (Emmitte, 2011;Christopoulos, 2014;Nickols and Conn, 2014) and in clinical development for the treatment of multiple CNS disorders (Berg et al, 2011;Jacquemont et al, 2011;Nickols and Conn, 2014;Lindemann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These selective mGlu 5 NAMs have shown exciting efficacy across preclinical models (Emmitte, 2011;Christopoulos, 2014;Nickols and Conn, 2014) and in clinical development for the treatment of multiple CNS disorders (Berg et al, 2011;Jacquemont et al, 2011;Nickols and Conn, 2014;Lindemann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been borne out empirically. For example, small molecules targeting allosteric sites of metabotropic glutamate receptors have been shown to exhibit excellent receptor subtype selectivity, which had not been achieved by ligands targeting the highly conserved glutamate binding site (Nickols and Conn 2014). Similarly, allosteric modulators of muscarinic receptors have been identified that exhibit selectivity superior to that attained by xanomeline or other orthosteric site M 1 receptor activators (Melancon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the seven-transmembrane region of the human mGlu5 receptor bound to the negative allosteric modulator (NAM) mavoglurant (AQ056 [methyl (3aR,4S,7aR)-4-hydroxy-4-[(3-methylphenyl)ethynyl]octahydro-1H-indole-1-carboxylate]; Novartis, Basel, Switzerland) was recently resolved (Doré et al, 2014). Together with a similar study that resolved the structure of mGlu1 receptors with the NAM, FITM [4-fluoro-N-(4-(6-(isopropylamino)pyrimidin-4-yl)thiazol-2-yl)-N-methylbenzamide] (Wu et al, 2014), important advances were made in the ability to design selective mGlu receptor modulators targeting the allosteric binding sites (Nickols and Conn, 2014).…”
Section: General Features Of Mglu5mentioning
confidence: 99%